Efficiency of price increasing taxation in the light of changes smoking behaviour of 13-15-year-old juveniles in Hungary (Academic Journal of Internal Affairs, 2020)
In some opinions, taxation is one of the most effective and cost-efficient interventions to reduce tobacco consumption. Objective: This study empirically tests the effects of price increasing taxation on the changes in smoking behaviour of 13-15-year-old juveniles in Hungary. Data: The Global Youth Tobacco Survey (GYTS) and Health Behaviour in School-aged Children (HBSC) were used to obtain data on the smoking behaviour of 29535 juveniles between 2002 and 2016. Design: From 2002 to 2016, the changes in price of tobacco products and smoking behaviour of 13-15-year-old juveniles were compared to each other. I have drawn conclusions about the possible effects of price increasing on the changes in smoking behaviour. Results: In one hand, it seems conceivable that cigarette price is an important determination of smoking initiation. However, it could not be clearly verified in this study. On the other hand, it seems to be proven that only the increase of taxes and cigarette prices are not able to reduce the proportion of daily and regularly (e.g. weekly) smoking juveniles in Hungary.
Keywords: smoking; juveniles; excise tax; price increase